Dual orexin receptor antagonists for treatment of insomnia: A systematic review and meta-analysis on randomized, double-blind, placebo-controlled trials of suvorexant and lemborexant - Khazaie, Habibolah; Sadeghi, Masoud; Khazaie, Sepideh; Hirshkowitz, Max; Sharafkhaneh, Amir (Frontiers in Psychiatry, 2022)
Study Objectives: Recent treatment guidelines for chronic insomnia recommend pharmacological and non-pharmacological therapies. One of the contemporary drug options for insomnia includes dual orexin receptor antagonist (DORA), such as suvorexant and lemborexant. We conducted a systematic review and meta-analysis for the treatment of insomnia with suvorexant and lemborexant based on randomized, double-blind, placebo-controlled Trials. Methods: We conducted a comprehensive search on three databases ( PubMed/Medline, Web of Science, and Cochrane Library) till August 14, 2021, without any restrictions to retrieve the relevant articles. The effect sizes were computed presenting the pooled mean difference or risk ratio along with 95% confidence interval of each outcome. Results: Our search showed eight articles (five for suvorexant and three for lemborexant). Results of diary measures, rating scales, polysomnography results, treatment discontinuation, and adverse events were measured. All efficacy outcome measures favorably and significantly differed in the suvorexant compared to placebo. Safety profile did not differ significantly except for somnolence, fatigue, and dry mouth. Important adverse events including hallucinations, suicidal ideation/behavior and motor vehicle accidents did not differ between suvorexant and placebo. All the efficacy outcomes significantly differed between lemborexant 5 and lemborexant 10 compared to placebo. Somnolence rate for lemborexant 5 and lemborexant 10 was significantly higher than placebo. Conclusions: The present meta-analysis reported that suvorexant and lemborexant are efficacious and safe agents for the patients with insomnia. Further data in patients with insomnia and various comorbid conditions are needed.